Efficiency, factor intensity and return to scale in Indian automobile workshops. (1st January 2013) - Panda, Debadutta Kumar
This study was conducted using survey data with an objective to understand the determinants of technical efficiency, factor intensity and return to scale in the four-wheeler automobile workshops in India. A random sampling technique was employed to select 372 cross-sectional sample workshops from four states of India. Data collection was done through structured pre-tested questionnaire. The sample workshops were further categorised into two groups, namely exclusive workshops and general workshops. Descriptive statistics, Cobb-Douglas production function and translog production function were used to analyse the data. The study revealed decreasing return to scale in the four-wheeler automobile workshops. The sample workshops were found to be capital intensive but the general workshops (who service all models of four wheelers from all manufacturers) were labour intensive. The significant determinants of technical efficiency of the workshops were engineering education and experience of the workshop owner, technical trainings undergone by the workshop owner, and period of existence of the workshop.